Foundation Financial Management Boarding School - Suranto, Suranto; Wazaitun, Watini (Journal of Advanced Islamic Educational Management, 2024)
This study aims to analyze the financial management of the Bustanul 'Ulum Islamic Boarding School Foundation Jaya Sakti Anak Tuha Central Lampung. This research uses descriptive research methods by collecting data through observation, interviews, and document analysis. The results showed that the financial management of the Boarding School had been carried out properly, including the budgeting process, the implementation of cash inflows and outflows, and evaluation through supervision and audits. The leadership of the Boarding School and its staff have carried out educational planning, expenditure planning, and income planning to ensure that the planned programs are in accordance with the vision, mission, and conditions of the institution. Financial inflows and outflows have been carried out effectively through the separation of activities, facilitating the implementation, supervision, and management of funds. Financial evaluation shows effectiveness in supervision, but transparency and community participation still need to be improved. The results of this study confirm the importance of transparent and accountable financial governance to support the sustainability of pesantren.